THE POETIC FUNCTION OF LIGHT IN UZBEK LYRICS (Scientific journal of the Fergana State University, 2024)
The article discusses the genesis and perfection of the use of light in Uzbek lyrics, the forms of its manifestation and the functions of expressiveness in modern lyrics. The connections in literary criticism on the use of light in a literary work are presented. Its place and significance in classical literature will also be determined. In new Uzbek literature, mainly in the literature of the new period after independence, especially in lyric poetry, various forms and manifestations of turning to light are more common. It is said that light, as one of the leading elements of the plot, is a motive, and its service in expressing the content of a work of art is being improved. 1) symbolic use of light; 2) descriptive (characteristic); 3) emotive functions are shown using the example of the poems of Halima Akhmedova. These light functions have been determined to be more common in multifunctional form than in general. In this place, the description of the image of light in the external world, the main guiding function in the expression of a poetic idea, is once again proven. Cases where the light motif is reflected through various forms and light sources are also explained. The fact that in the literature of the new era, where spiritual and secular relations are combined, the attitude towards light has acquired its charm and emotive, in which light appears on the basis of the motive of expressing an artistic idea, and has fulfilled the functions of characterizing the image, emotive and even in the form of an image, it has been proven that all this is due to the fact that the expression of light in Uzbek lyrics has its own genesis and perfection.С